THE EFFECTIVENESS OF RECEIVING RETRIBUTION FROM FISH AUCTION FROM TPI CIWARU IN INCREASING REGIONAL REVENUE (PAD) OF SUKABUMI DISTRICT FROM THE FISHERY SECTOR - Andriani, Ence Melisa; Mulyadi, Andi; Sampurna, Rizki Hegia (DIA: Jurnal Administrasi Publik, 2023)
Regional Retribution is a regional levy as a payment for services or the granting of certain permits specifically provided and/or granted by the local government for the benefit of individuals or entities. This study aims to determine the effectiveness of the levy for receiving fish auctions at TPI Ciwaru in increasing local revenue (PAD) of Sukabumi Regency from the marine sector, and what are the obstacles that occur in the process. This research method uses a qualitative descriptive method and an analysis of the effectiveness measurement according to James L. Gibson. By collecting data using observation, interviews and documentation. The result of this study is that the acceptance of fish auction fees at TPI Ciwaru cannot be said to be effective. Revenue from fish auction fees at TPI Ciwaru has not been effective, as evidenced by the fish auction fees which are still low compared to the potential and large production value each year and never reach 1% according to the applicable local regulations.